Adoption of cassava technologies: Constraints, strategies and impact - Henry, Guy (1991)
An attempt is made to identify and analyze cassava technology adoption constraints (multiplication, var. diffusion, institutional, political, structural) and to describe an integrated research strategy that leads toward a more successful impact. Issues that should be considered in the research agenda that will contribute to alleviate constraints are true cassava seed, specific breeding objectives, farmer participatory research, preproduction plots, and on-farm cassava stake multiplication. The efficient development of improved technology and optimization of technology diffusion help increase the area planted to new var., the no. of farmers using improved production and processing technologies, and the no. of cassava processing plants. Examples of cassava adoption and impact are detailed, namely the adoption of Rayong 3 in Thailand and the integrated cassava drying projects in Latin America. Relatively too much emphasis has been placed on production technology development and too little on alleviating basic constraints on the adoption process, resulting in reduced technology impact. The strategy used by CIAT integrates technology and adoption research. Quality of adoption research is also important; the integration of technology and adoption research is the key to successful diffusion and impact. This integrated approach must involve complete collaboration of farmer and researcher during the entire research process. (CIAT)